Behind the Scenes of Adaptive Learning: A Scoping Review of Teachers’ Perspectives on the Use of Adaptive Learning Technologies - Patricia D. Simon; Lily Min Zeng (Education Sciences)
Adaptive learning technologies are emerging educational tools that personalize instruction and tasks to meet students’ current ability levels. Despite their increasing prevalence, the present discourse on adaptive learning software focuses on the technical aspects of adaptive learning systems without accounting for other factors that impact their use in classrooms. In acknowledgment of the importance of teachers’ roles in the implementation of educational tools, this review examined studies about teachers’ perspectives on the use of adaptive learning technologies in their courses. A systematic search was conducted in four databases (ERIC, Academic Search Complete, Google Scholar, and Taylor Francis Online). Twenty-nine full-text articles were retained for analysis. A hybrid of deductive and inductive approaches was applied to analyze the data, using the factors described in the Technology Acceptance Model and its extensions as a guide. The findings showed that teachers who saw the long-term benefits of using adaptive learning technologies were more willing to invest time and effort to learn and use the tools in their classes. Barriers identified were the scant professional development opportunities for teachers, the programs’ complexities, and the demands on teachers’ time. To make adaptive learning programs work, teachers must be on board as co-designers and content creators, and they require ongoing technical and institutional support and sufficient preparation in teacher education programs.